Developing the employability competency for the tourism and hotel industry in Hong Kong - Yip, Lilian Lai Hang (2017)
In 2000, Hong Kong had a major educational reform, which aimed to address the inadequacies of the previous education system in order to enable the majority of Hong Kong’s population to achieve lifelong learning and an all-round education. These are also the overall aims of education in Hong Kong for the 21st century. A new education structure and new curricula for primary and secondary schools were some of the focuses of the reform. The tourism and hotel industry is one of the four pillar industries in Hong Kong. As a growing service industry, it relies heavily on the quality of their employees and the stability of manpower. However, this industry has been facing difficulties in recruiting and retaining qualified employees. Many studies have been conducted to discover the ideal employability competency and to develop strategies to attract and retain the right employees. Through the study of employability theories and in-depth interviews with education practitioners in the tourism and hotel industry, this research study links-up two knowledge areas of employability competency for the tourism and hotel industry and the generic competency development in primary and secondary school education in Hong Kong. The results reveal that previous studies have not resolved human capital problems, because these problems are rooted in the incompetence in generic skills, values and attitudes of individuals. This study highlights the foundational role of generic competency in employability. It proposes that a generic competency, which has to be nurtured from a young age, is essential for employability. The findings inspired an extended concept of employability and contributed to a new generic competency structure. For primary and secondary school education, this study proposes the incorporation of a refined generic competency component in the school curriculum, along with strategies to mitigate possible barriers of implementation. The proposed employability structure can also be used by employment consultation services or serve as a recruitment, training, development and retention guide in the tourism and hotel industry. These proposals could nurture new generations with the required employability competency for the tourism and hotel industry, meeting the challenges of the 21st century.